Cretaceous Intraplate Contraction in Southern Patagonia: A Far‐Field Response to Changing Subduction Dynamics?. Issue 9 (6th September 2018) - Gianni, G. M.; Navarrete, C.; Liendo, I.; Díaz, M.; Giménez, M. E.; Encinas, A.; Folguera, A.
Abstract: The origin, extent, and timing of intraplate contraction in Patagonia are among the least understood geological processes of southern South America. Particularly, the intraplate Deseado fold‐thrust belt (FTB), located in the Patagonian broken foreland (47°–48°30′S), is one of the most enigmatic areas. In this belt, time constraints on tectonic events are limited and synorogenic deposits have not been documented so far. Furthermore, the driving mechanism for intraplate contraction remains unknown. In this study, we carried out a structural and sedimentological analysis. We report the first syntectonic deposits in this area in the Baqueró (Aptian) and Chubut (Cenomanian/Campanian) groups and a newly found unit referred to as the Albian beds (109.9 ± 1.5 Ma). Thus, several contractional stages in late Aptian, Albian, and Cenomanian‐Campanian are then inferred. We suggest that the Deseado FTB constituted the southernmost expression of the early Patagonian broken foreland in Cretaceous times. Additionally, we analyzed the spatiotemporal magmatic arc behavior as a proxy of dynamic changes in the Andean subduction during determined stages of intraplate contraction. We observe a significant arc broadening from ~121 to 82 Myr and magmatic quiescence after ~67 Ma. This is interpreted as a slab shallowing to flattening process. Far‐field tectonic forces would have been produced by increased plate coupling linked to the slab flattening as indirectly indicated by the correlation between Cretaceous arc expansion and intraplate contraction. Finally, the tectonic evolution of the Deseado FTB favors studies supporting inception of Andean shortening since Cretaceous times. Key Points: We document Cretaceous syntectonic deposits linked to intraplate contraction in Southern Patagonia This process took place in concert with a significant magmatic arc expansion Intraplate contraction in southern Patagonia could be the aftermath of an ancient flat subduction event